Endoscopic ablation for malignant lung lesions: current techniques, unmet needs, and future directions - Fernandez-Bussy, Sebastian; Gutierrez-Gallegos, Paola; Yu Lee-Mateus, Alejandra; Brock, Judith; Quevedo-Salazar, Renata; Abia-Trujillo, David; Husta, Bryan C.; Vu, Linh H.; Sun, Jiayuan; Herth, Felix (Respiration, 2025)
Background: Lung cancer remains the leading cause of cancer-related mortality worldwide. Although surgical resection and stereotactic body radiation therapy are standard treatment options for early-stage disease, both are limited by procedural morbidity and ineligibility among high-risk patients. Similarly, percutaneous approach with image-guided ablation is associated with pneumothorax and pleural injury. Advances in navigation, imaging, and device design have enabled endoscopic ablation to emerge as a minimally invasive technique capable of targeting peripheral and central lesions under real-time image guidance. Summary: Endoscopic ablation techniques, comprising radiofrequency, microwave, laser, vapor, cryoablation, photodynamic therapy, pulsed-electric field ablation, and intralesional chemotherapy, enable precise bronchoscopic delivery of localized therapy. Early feasibility, safety, and clinical data demonstrate high technical success, favorable short-term safety, and potential immunologic synergy when combined with systemic therapy. Nonetheless, several challenges remain, including limited access to subsegmental lesions, variability in ablation margins, and lack of long-term outcomes. Despite these limitations, ongoing advances in device design, navigation, and imaging, such as robotic-assisted bronchoscopy and cone-beam computed tomography, are enhancing the procedural precision and therapeutic reach. This review synthesizes current evidence on endoscopic ablation, focusing on emerging technologies, clinical applications, and key research gaps. Key Messages: Endoscopic ablation represents a promising, lung-sparing treatment for lung malignancies. Ongoing technological advances in navigation, imaging, and integration are enhancing its applicability in local tumor control. Large, prospective trials are required to validate oncologic efficacy, optimize procedural parameters, and establish endoscopic ablation’s role within multimodal lung cancer management.
Veröffentlicht: 27. Oktober 2025
Gesehen am 26.01.2026